Catalase-driven protein microtube motors with different exterior surfaces as ultrasmall biotools. Issue 19 (15th September 2021) - Umebara, Mizuki; Sugai, Natsuho; Murayama, Kohei; Sugawara, Tomonao; Akashi, Yushi; Morita, Yoshitsugu; Kato, Ryo; Komatsu, Teruyuki
Abstract : We report the synthesis of catalase-driven protein microtube motors with different exterior surfaces. Their abilities of bacteria capture, reaction enhancement by self-stirring, and velocity control with light irradiation were highlighted. Abstract : This report describes synthesis of catalase-driven protein microtube (MT) motors with different exterior surfaces, highlighting their abilities of bacteria capture, reaction enhancement by self-stirring, and velocity control with light irradiation. Common precursor MTs with an internal wall of avidin (Avi MTs) were prepared using template synthesis with layer-by-layer (LbL) assembly in a track-etched polycarbonate (PC) membrane. Subsequently, (i) avidin–biotin complexation immobilized biotinylated catalase in the liberated MTs, and (ii) the outside wall was covered with lectins, enzymes, or Au nanoparticles (AuNPs). The designed MTs of four kinds (1.2 μm outer diameter, 24 μm length) were self-propelled in aqueous H2 O2 solution powered by O2 bubble ejection from the terminal opening. The swimming (concanavalin A)-wrapped MTs captured Escherichia coli bacteria. The self-stirring motion of (α-glucosidase)-coated MTs promoted the hydrolysis reaction of α-glucoside linkage. The similar (horseradish peroxidase)-covered MT motors used H2 O2 as both a propulsion fuel and an oxidizing agent. Furthermore, the velocity of the swimming AuNP-bound MTs can be modulated by visible light irradiation. Photothermal heat generation by AuNPs increased the Cat enzyme activity. Notably, proteases digested the four MTs, demonstrating sufficient biodegradability. These results showed that the catalase-driven MT motors with different outer surfaces act as ultrasmall moving biotools.